Understanding the relationship of storm‐ to large‐scale environment in the monsoon trough region: results inferred from long‐term radar and reanalysis datasets. (15th November 2021) - Jha, Abhishek Kumar; Das, Subrata Kumar; Deshpande, Sachin M.; Murali Krishna, U. V.
Abstract: Monsoon trough (MT) convection exhibits multiscale spatial variability ranging from cellular storms to large organized convective systems. Understanding the relationships between storm‐scale convection and the large‐scale environment is crucial for accurately representing the properties and effect of convection in climate models. We investigate these relationships using nine wet seasons (June–September of 2009–2017) of S‐band radar observations over a tropical location (Kolkata) in the Indian summer monsoon trough region. A Lagrangian‐based objective cell‐tracking method, Thunderstorm Identification, Tracking, Analysis, and Nowcasting (TITAN), is applied to the volumetric reflectivity data to identify and track the convective storms. ERA5 hourly reanalysis products from the European Centre for Medium‐Range Weather Forecasts (ECMWF) are utilized for the field variables representing the large‐scale environment. We focus on the relationships of radar‐derived storm properties with large‐scale dynamic, thermodynamic, and stability variables such as convergence, mid‐level humidity, convective available potential energy (CAPE), and convective inhibition (CIN). Storm‐scale convection shows a selective nature, characterized as embedded cells in their unique environment. Furthermore, storms are classified as storm cells (simple and intense) and multicellular (linear and nonlinear) based on their geometrical properties and intensity. MT convection is predominantly composed of storm cells and characterized by an environment of moist mid‐level, low‐to‐moderate CAPE, low CIN, and strong dynamic forcing, that is, vertical ascent. In dry and weak dynamic forcing (i.e., subsiding atmosphere) with high CAPE and CIN, the highest rain intensity is associated with a few linear and nonlinear multicellular storms. In the development of such major linear and nonlinear multicellular storms over the eastern flank of the MT, the mid‐troposphere acts as a dry capping inversion. It is observed that the storm‐scale convection varies with the large‐scale dynamic forcing. During weak (strong) dynamic forcing conditions, the CAPE (mid‐level humidity) relates well with the observed storm‐scale convection. Abstract : Storm‐ to large‐scale environment relationships are examined using long‐term observations. The study evidenced a "natural selection" effect of mid‐level humidity. A random to deterministic relationship is observed during weak and strong synoptic forcing. Scatter plots between VMFC and (a) CAPE, (b) mid‐level humidity (RH650 ), and (c) CIN are presented where dotted, solid, and dashed lines show 95 percentile, median, and 5 percentile values, respectively.